14 Not having the real support that we need: patients experiences with ambiguity of systemic lupus erythematosus and erosion of social support. (April 2019) - Leung, Jerik; Baker, Elizabeth; Kim, Alfred H
Abstract : Background: A hallmark of SLE is the paroxysmal disease course with symptoms fluctuating unpredictably both across different individuals and within individual cases. Importantly, the patient-specific experience of living with SLE is underreported, particularly when studying factors associated with health-related quality of life (HRQOL). Recent work has suggested that biomedical interventions are only partially predictive of HRQOL measures. The patient specific experience studied using qualitative methods is a necessary initial step to uncover additional root causes of poor HRQOL in SLE populations as patient experiences add richness and depth to a topic of inquiry not possible through quantitative methods. Methods: Consented adult patients with American College of Rheumatology- or Systemic Lupus International Collaborating Clinics-classified SLE were recruited for this study during their scheduled clinic visits. Ten semi-structured interviews were conducted across six participants. Interviews were audio recorded, transcribed, and analyzed using an iterative process where all data were first grouped based on the major questions of the study and then coded using an open coding scheme, allowing for identification of key issues based on patient experiences. Findings were presented to an interactive public forum with SLE patients, family members and friends of individuals with SLE, and health care professionals and assessed for accuracy and credibility. Results: Four major factors that influence HRQOL emerged from the interviews: 1) ambiguity, inconsistency, and lack of symptom predictability due to SLE disease courses, 2) poor communication with family/friends/partners, and poor bi-directional communication between health care providers and patients (informational support), 3) lack of validation for patients experiences (appraisal support), and 4) problematic aspects of social support including negative support and patients inability to reciprocate support due to role changes. Data also indicate a reciprocal association between appraisal and informational sources of support. Conclusions: Findings indicate that inadequate appraisal and informational support from informal and formal sources and ambiguity are particularly salient factors influencing HRQOL among SLE patients. Further investigation is needed to fully elucidate associations between biological (unpredictable of SLE symptoms), social (informational and appraisal sources of social support), and community level (public awareness campaigns) factors influencing disease. Findings also point to the necessity of integrating community organizations, physicians, and friends and family of patients with SLE into capacity building interventions aimed at improving HRQOL. Funding Source(s): Summer Undergraduate Research Award (Washington University in St, Louis)